SaveMe: Client-Side Aggregation of Cloud Storage - Song, Gyuwon; Kim, Suhyun; Seo, Dongmahn (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2015)
Nowadays, there are many cloud storage service providers and many of them provide significant amounts of free storage. It is desirable for users to be able to manage the storage space available to them as a single unified space. Otherwise, user files will be scattered over many different providers, negating the advantage of using cloud storage. Another important concern of users is that their data is at the disposal of the service providers. Lastly, in contrast to the hype of extremely high availability, accidents tend to happen and even the most available cloud services are not accessible many times per year or even per month. SaveMe is designed to solve all of these issues, providing aggregation, security, and higher availability purely from the client side. It is the first approach to address all three issues without any additional server component. To achieve these goals, SaveMe is building a single virtual volume by combining public and private cloud storage. In SaveMe, every file is fully encrypted, erasure coded, and distributed. For better security and privacy, all data processes are performed on the client side, unlike the case of conventional cloud storage services. The logical volume of SaveMe is extensible due to a flexible data and volume model. The authors also tested the performance of SaveMe in comparison with those of existing services. SaveMe showed above average performance in terms of the speeds of uploading or downloading files. Furthermore, data availability evaluation clearly demonstrates that the availability of SaveMe is an order of magnitude higher than those of other commercial cloud storage services.